Descolonizar la ética y otros problemas geopolíticos-pedagógicos del conocimiento (2021)
This essay shows the role of coloniality in the contemporary configuration of the geopolitics of knowledge, the naturalization of certain positions or places of enunciation, and the occlusion of others generally reduced to the order of “the knowable.” This scenario poses unavoidable problems in a context where, in the name of the European Enlightenment and its reversals, some inheritances of thought are imposed to the detriment of other local premises, just as failed anthropophagies or excessive assimilations due to poor digestion can be promoted. Thus, it becomes important to outline a decolonizing ethic from which to question and respond to the problems posed by those positions that seek to redirect the epistemic debate to the pace imposed by the European legacy. In this quest, the ethical, the political, and the educational are joined in a subversive gesture that is woven with necessarily open struggles in the face of the panorama that contemporary thought offers.